STUDY OF FIXED POINT THEOREM FOR BANACH OPERATOR PAIR OF T- CONTRACTION MAPPINGS IN CONE METRIC SPACES - Tiwari, Surendra Kumar (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
The purpose of this paper is to establish and extend the concept of T-Rhoades contraction to the case of Banach operator pairs of mappings in the setting of complete cone metric spaces without the assumption of normality condition. Keywords: Cone metric space, complete cone metric space, fixed point, common fixed point, T- Rhoades contraction. Banach operator pair. 2010 Mathematical subject classification: Ex:47 H10